Beetle Luciferases: Colorful Lights on Biological Processes and Diseases - Viviani, Vadim R. [UNESP] (2006)
Departamento de Biologia, Celular e Molecular Instituto de Biociências Universidade Estadual Paulista (UNESP), Rio Claro, SP 13506-900